1985
DOI: 10.1104/pp.79.4.1048
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Citrus Fruit to Mass Transport of Water Vapor and Other Gases

Abstract: The resistance of oranges (Citrus sinensis L. Osbeck) and grapefruit (Citrus paradisi Madf.) to ethylene, 02, CO2, and H20 mass transport was investigated anatomically with scanning electron microscope and physiologically by gas exchange measurements at steady state. The resistance of untreated fruit to water vapor is far less than to ethylene, CO2 and 02. Waxing partially or completely plugs stomatal pores and forms an intermittent cracked layer over the surface of fruit, restricting transport of ethylene, 02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 9 publications
2
45
0
1
Order By: Relevance
“…Likewise, water potential and turgor pressure of freshly harvested fruit reflected turgid nonstressed cells, indicating that fruit were not stressed at harvest and, therefore, that they did not develop non-chilling peel pitting as a consequence of re-hydration, which has been shown to induce this disorder (Alférez et al, 2003). Waxes may have a more marked effect on inhibiting transport of gases than transport of water through the cuticle in citrus fruit (Ben-Yehoshua et al, 1985). The mode of action by which external or internal gases may alter the susceptibility of citrus fruit to develop peel damage remains unknown, though postharvest treatments modifying internal gas composition or the O 2 environmental levels may also modify non-chilling peel pitting susceptibility (Petracek et al, 1998;Ben-Yehoshua et al, 2001;Porat et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, water potential and turgor pressure of freshly harvested fruit reflected turgid nonstressed cells, indicating that fruit were not stressed at harvest and, therefore, that they did not develop non-chilling peel pitting as a consequence of re-hydration, which has been shown to induce this disorder (Alférez et al, 2003). Waxes may have a more marked effect on inhibiting transport of gases than transport of water through the cuticle in citrus fruit (Ben-Yehoshua et al, 1985). The mode of action by which external or internal gases may alter the susceptibility of citrus fruit to develop peel damage remains unknown, though postharvest treatments modifying internal gas composition or the O 2 environmental levels may also modify non-chilling peel pitting susceptibility (Petracek et al, 1998;Ben-Yehoshua et al, 2001;Porat et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In citrus fruit, it has been shown that the amount, composition and structure of the epicuticular wax varies among cultivars, changes with fruit development, maturation and age (Freeman et al, 1979;El-Otmani and Coggins, 1985a;Sala et al, 1992), and has an effect on both water loss (Albrigo, 1972a) and transport of gases through the cuticle (Ben-Yehoshua et al, 1985;El-Otmani et al, 1986). Furthermore, redistribution of epicuticular wax layer may improve physical barriers to pathogen penetration and reduce disease incidence caused by Penicillium digitatum (Pers.:Fr.)…”
Section: Introductionmentioning
confidence: 99%
“…Burg and Burg (1965b) and then Solomos (1987) developed relationships between rates of ethylene production by fruit and the internal concentrations and these relationships were surprisingly found similar across many fruit species. However, more has to be learned about the retention and release of ethylene in plant tissues in relation to its resistance towards the diffusion across the boundaries of fruit and physiological activity of ethylene bound to its receptor (Ben-Yehoshua et al 1985;Goldschmidt et al 1993). So, to get better understanding of ethylene emission by tomato fruit Genard and Gouble (2005) developed a simulation model called 'ETHY'.…”
Section: Role Of Ethylene In Regulation Of Fruit Ripeningmentioning
confidence: 99%
“…But, usually, this aspect has not been taken into consideration in the studies dealing with resistance of the fruits to diffusion and exchange of gases (Ben-Yehoshua et al 1985). So, more has to be learned about the retention and release of bound ethylene in plant tissues in relation to physiological activity of ethylene (Goldschmidt et al 1993).…”
Section: Ethylenementioning
confidence: 99%